2022
DOI: 10.2500/aap.2022.43.220037
|View full text |Cite
|
Sign up to set email alerts
|

Cat allergy in children and the effect of the COVID-19 pandemic

Abstract: Background: Cat allergen is among the most common household allergens and can cause respiratory allergies and anaphylaxis in children. Objective: The aim of this study was to evaluate the characteristics of cat allergies in children and the impact of the coronavirus disease 2019 (COVID-19) pandemic on these characteristics. Methods: The study included pediatric patients with cat allergen sensitization demonstrated by skin-prick test (SPT) over a period of 2 years: 1 year before and 1 year during the pandemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
5
5
2
Order By: Relevance
“…Research has demonstrated that numerous patients sensitized to cats and dogs also exhibit sensitization to additional respiratory allergens [6, 17, 18]. In the present study, we observed polysensitivity with nearly 85% of patients in both sensitization groups.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…Research has demonstrated that numerous patients sensitized to cats and dogs also exhibit sensitization to additional respiratory allergens [6, 17, 18]. In the present study, we observed polysensitivity with nearly 85% of patients in both sensitization groups.…”
Section: Discussionsupporting
confidence: 68%
“…According to Kang et al [21], 34% of patients sensitized to cats developed symptoms after exposure to cats, while 22% of patients sensitized to dogs developed symptoms after exposure to dogs. In another study conducted on children in Turkey, 44.5% of the patients who were sensitive to cats were symptomatic [6]. In our study, 60% of patients with cat sensitivity and 22.5% with dog sensitivity were symptomatic.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations